And then you're dead : what really happens if you get swallowed by a whale, are shot from a cannon, or go barreling over Niagara - Cassidy, Cody; Doherty, Paul (Penguin Books, 2017)
"A gleefully gruesome look at the actual science behind the most outlandish, cartoonish, and impossible deaths you can imagine What would happen if you took a swim outside a deep-sea submarine wearing only a swimsuit? How long could you last if you stood on the surface of the sun? How far could you actually get in digging a hole to China? Paul Doherty, senior staff scientist at San Francisco's famed Exploratorium Museum, and writer Cody Cassidy explore the real science behind these and other fantastical scenarios, offering insights into physics, astronomy, anatomy, and more along the way. Is slipping on a banana peel really as hazardous to your health as the cartoons imply? Answer: Yes. Banana peels ooze a gel that turns out to be extremely slippery. Your foot and body weight provide the pressure. The gel provides the humor (and resulting head trauma). Can you die by shaking someone's hand? Answer: Yes. That's because, due to atomic repulsion, you've never actually touched another person's hand. If you could, the results would be as disastrous as a medium-sized hydrogen bomb. If you were Cookie Monster, just how many cookies could you actually eat in one sitting? Answer: Most stomachs can hold up to sixty cookies, or around four liters. If you eat or drink more than that, you're approaching the point at which the cookies would break through the lesser curvature of your stomach, and then you'd better call an ambulance to Sesame Street"--